The Role of Emerging Digital Technologies in the Apparel Industry of Pakistan - Malik, Alveena; Imran, Muhammad (South Asian Review of Business and Administrative Studies (SABAS), 2022)
Abstract Purpose: Current study examines the relationship of industry 4.0 on firm performance through process mediation of employee involvement and mass customization capabilities. The motivation to conduct the current study was driven by the decreasing trend of Pakistan apparel exports and the inconsistent findings in the literature on the relationship among variables. Design/Methodology/Approach: Population of the study are the export members firms of HS code 61 and HS code 62 apparel manufacturing firms. From 1564 firms 10000 senior and middle management identified as a population. Structural equation modeling (SEM) was used to test the research model. Findings: The results reveal that industry 4.0 technologies positively impacted firm performance. Study findings also show the process mediation of employee involvement and mass customization capability between big data and firm performance. Implication/Originality/Value: To the best author's knowledge, this is the first attempt to examine the process mediation of employee involvement and mass customization capability on the relationship between industry 4.0 and Pakistan apparel firm performance.